PENGARUH PENGGUNAAN MEDIA VIDEO ANIMASI TERHADAP KEMAMPUAN SISWA DALAM PEMBELAJARAN PROSES FOTOSINTESIS - Rendi Marlianda; Muhammad Subhan; Yoli Angela Rosanti (STKIP Subang, 2024)
The problem of this research is the low ability of students in science content, especially in the photosynthesis process material, this is proven based on the results of daily questions. The purpose of this research is to find out whether there is an influence of the use of video animation media on students’ abilities in learning the photosynthesis process. This type of research was the experimental method. The design of this research was quasi-experimental. The place of this research was SDN 10 Koto Baru and SDN 04 Koto Baru. This research was used at the second semester of the 2024/2025 academic year. The samples for this research were 40 students. From the results of the dependent sample t-test, the significance obtained was 0,001 < 0,005. So it can be concluded that there is an influence from the use of animated video media on students’ abilities in learning the photosynthesis process based on the pretest and posttest results in this research that the use of animated video media has a good influence. Towards students’ abilities. Animasi video media can be used by educators as a supporting medium in the learning process and can increase students’ concentration in participating in teaching and learning activities.